2017
DOI: 10.1071/ch16586
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Magnetic Studies on a Series of Two-Dimensional Iron(II) Framework Materials with Varying Ligand Characteristics

Abstract: Targeting the general (4,4)-grid structural motif, we have prepared seven new coordination polymers in the general family [Fe(NCX)2(L)2]·(guest) (L = bis-pyridyl-type bridging ligands; X = S, Se) as an extension of the well-established spin crossover framework (SCOF) family. In all cases, the (4,4)-grid topology is formed by the bridging of octahedral iron(ii) sites in the equatorial plane by bis-pyridyl ligands of varying length, flexibility, and intermolecular interaction capacity. In particular, the six lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The spin crossover properties of these compounds turned out to be highly dependent on the solvent content which in turn was intimately interacting with the pina ligand via H-bonding. Similarly, the not-SCO-active 2D compound [Fe II (NCS) 2 ( pina ) 2 ]·2­(CH 3 CN) not only presents H-bonds between the amide moieties and the acetonitrile molecules but also between the pina ligands through CO···HN contacts . Here, we have implemented, for the first time, the bridging pina ligand to build a 3D structure that exhibits accessible void volume, ca.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spin crossover properties of these compounds turned out to be highly dependent on the solvent content which in turn was intimately interacting with the pina ligand via H-bonding. Similarly, the not-SCO-active 2D compound [Fe II (NCS) 2 ( pina ) 2 ]·2­(CH 3 CN) not only presents H-bonds between the amide moieties and the acetonitrile molecules but also between the pina ligands through CO···HN contacts . Here, we have implemented, for the first time, the bridging pina ligand to build a 3D structure that exhibits accessible void volume, ca.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the not-SCO-active 2D compound [Fe II (NCS) 2 (pina) 2 ]•2(CH 3 CN) not only presents H-bonds between the amide moieties and the acetonitrile molecules but also between the pina ligands through CO•••HN contacts. 30 Here, we have implemented, for the first time, the bridging pina ligand to build a 3D structure that exhibits accessible void volume, ca. 40%, where methanol molecules can be trapped affording an infinite lattice of H-bonds.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors have reported a poly-knotted 3D structure after coordination of 4,4'-bptz with Cd(II) metal ions. 81 4,4'-bptz has been coordinated to more divalent metal ions, such as Mn(II), 82 Fe(II) 83 and Ni(II), 73 to afford neutral CPs. In the 3D CP [Mn(4,4'-bptz)(N3)2], 84 In the ten last years, the adsorption properties of 4,4'-bptz-based MOFs have been thoroughly investigated.…”
Section: 6-bis(4-pyridyl)-1245-tetrazine (44'-bptz)mentioning
confidence: 99%
“…[15] Stuart Batten, Keith Murray, David Turner, and Glen Deacon at Monash University present transition metal thiocyanate complexes of picolylcyanoacetamides, [16] and Suzanne Neville from Sydney brings us an investigation into the structure and magnetic properties of a series of two-dimensional iron(II) framework materials. [17] Peter Junk, currently Nevitt Professor of Chemistry at JCU where Len was based for the bulk of his career, reports on the synthesis and structures of rare earth 3-(4 0 -methylbenzoyl)-propanoate complexes and their properties as new corrosion inhibitors. [18] Deanna D'Alessandro (Sydney), who undertook her Ph.D. at JCU with Richard Keene, presents findings of the in situ spectroelectrochemical investigation of ruthenium(II) complexes with bispyrazolyl methane triarylamine ligands.…”
mentioning
confidence: 99%